The economics of beer - Swinnen, Johan F. M., 1962- (Oxford : Oxford University Press, 2011)
The first economic analysis of the beer market and brewing industry, this volume examines the history and consumption of beer, industrial organisation, and new beer markets. It presents global developments as well as country studies from Europe, the US, China, Russia, and India.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Beer industry